1993
DOI: 10.1021/ic00055a022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and reactivity of Lewis acidic cyclopentadienyltitanium dithiolate complexes

Abstract: The reaction of CpTiCl3 with 1,3-propanedithiol yields the mononuclear Ti(IV) species CpTi(SCH2CH2CH2S)Cl (1) . This diamagnetic chelate complex crystallizes in the space group Pi with a = 8.729 (4) A, b = 10.114 (2) A, c = 6.620 (4) A, a = 90.70 (4)°, ß = 109.35 (4)e, y = 97.02 (4)ß, V = 546 (1) A1 23 45678, and Z = 2. Subsequent reaction of 1 with 1 equiv of sodium benzenethiolate yields the species CpTifSC^CI^CF^SXSCeHs) (2). This compounds crystallizes in the space group P2i with a -7.506 (2) A, b = 19.761… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 5 publications
0
32
0
1
Order By: Relevance
“…The T-donor ability of the oxygen atoms competes with the cyclopentadienyl ring for metal d-orbitals and thus facilitates the loss of CpH and the formation of 4. Although no direct evidence has been obtained for the proposed intermediates, the known species 7 and the established ability of Ti three-legged piano stool complexes to bind additional donor ligands are consistent with these propositions (2).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The T-donor ability of the oxygen atoms competes with the cyclopentadienyl ring for metal d-orbitals and thus facilitates the loss of CpH and the formation of 4. Although no direct evidence has been obtained for the proposed intermediates, the known species 7 and the established ability of Ti three-legged piano stool complexes to bind additional donor ligands are consistent with these propositions (2).…”
Section: Discussionmentioning
confidence: 85%
“…In the case of 3 this formulation was also confirmed crystallographically (vide infra). In a recent report we demonstrated that substitution reactions involving CpTiC13, thiol, and imidazole proceed through a radical mechanism involving a Ti(II1)-imidazole complex intermediate (4). The formation of 1-3 from the diol-imidazole reactions may also proceed through this intermediate.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…B. CdSe/CdS und CdSe/ ZnS. [4,5] Im Vergleich zu den Kernen wurde eine erhebliche Steigerung der Emissions-Quantenausbeute und eine gröûere Stabilität gegen Oxidation beobachtet. Diese verbesserten Nanokristalle sind als neuartige Fluoreszenzmarker in biologischen Anwendungen mit deutlichen Vorteilen gegenüber traditionellen Fluoreszenzfarbstoffen eingesetzt worden.…”
unclassified